Thursday

April 24, 2014

April 24, 2014

Posted by **anonymous** on Tuesday, April 9, 2013 at 12:41am.

- Algebra 2 -
**Bosnian**, Tuesday, April 9, 2013 at 1:45am- 2 ( 3 x + 2 y - 3 ) > 12

- 2 * 3 x - 2 * 2 y - 2 * ( - 3 ) > 12

- 6 x - 4 y + 6 > 12

- 4 y > 12 + 6 x - 6

- 4 y > 6 x + 6

- 4 y > 6 ( x + 1 ) Divide both sides by - 4

If you multiply or divide both sides of an inequality by a negative number, you must reverse the direction of the inequality sign!

y < - 6 ( x + 1 ) / 4

y < -3 ( x + 1 ) / 2

y < 3 x / 2 - 3 / 2

- Algebra 2 -
**Bosnian**, Tuesday, April 9, 2013 at 1:48amremark:

y < - 6 ( x + 1 ) / 4

are same as

y < 6 ( x + 1 ) / - 4

**Related Questions**

algebra - how do I do this Solve for x. 3x – 2y = 6 Add 2y to both sides and ...

algebra - needing help with is problem solve for x: 3x-2y=-6 here is my solution...

Pre Cal.--Check my work? - Solve the system of equations: x - y - z = 2; x + 2y...

Algebra - Solve the system of inequalities. y<2x+4 -3x - 2y> 6 So I just ...

Algebra - Solve the following system of linear inequalities by graphing. x-3y>...

Algebra - To solve the system of equations, which expression could be ...

maths - use the substitution method to solve the linear system. 1. 3x=9 -x+2y=9 ...

Math - can someone check to see if these inequality equations are the correct ...

algebra - if you have the sign of > or < does this also mean = ???? so ...

algebra 2 - 1) 2a+c=-10 b-c=15 a-2b+c=-5 2) x+y+z=3 13x+2x=2 -x-5z=-5 3)x-y+3z=3...